US Army doctrine foundations review and development of recommendations on initiation of US Army doctrinal studies for beginners in the context of Ukrainian Armed Forces transition towards NATO standards - Rossiytsev, Victor (Social Development and Security, 2020)
This article could be interesting for defense professionals engaged in research and implementation of modern standards and principles of leading NATO countries. The United States is a leading NATO country and its armed forces have a significant impact on the current state and prospects of this political-military alliance. The article focuses on the US Army doctrine which in terms of significance, could be equated to the smaller nation-level Armed Forces doctrinal publications. Currently, the US Army doctrine is open and most part of it available for unrestricted access from the Internet. Thousands of doctrinal and other military publications provide an exhaustive list of answers on current standards of leading military forces functioning in peacetime and wartime environment. The range of themes varies from the interaction between the various components of the military forces and various civil agencies in unified operations to the holistic principles of healthy eating and work-sleep balance for an individual soldier. This paper is written in the light of the full revision of the of the Ukrainian Armed Forces doctrine. The reform envisages the development of 272 brand new doctrinal publications by the end of 2020. These doctrines are to consider the lessons learned in Allied Forces Operation (Anti-Terrorist Operation) in eastern Ukraine and the requirements of both existing national regulations and the standards of leading NATO member countries. Moreover, this reform must not to reduce the existing level of effectiveness of Armed Forces operations in the Eastern Ukraine. Exploration of foreign doctrine, however, requires from the researcher not only proficiency in foreign language and relevant military terminology, but also the knowledge of the respective doctrinal foundations. This article offers a minimum set of knowledge that will allow researcher to confidently work with US Army doctrine and is to facilitate its further learning process.